Physiological responses to rifle carriage during roller-skiing in elite biathletes - Kårström, M. J.; McGawley, K.; Laaksonen, M. S. (Frontiers in Physiology, 2019)
Purpose: This study aimed to investigate the physiological factors affected by rifle carriage during biathlon skiing performance, as well as the sex differences associated with rifle carriage.